Supercritical fluid technology for solubilization of poorly water soluble drugs via micro- and naonosized particle generation - Shashi Kiran Misra; Kamla Pathak (International Association of Physical Chemists (IAPC), 2020)
Approximately two-third of the compounds in the pharmaceutical industry were developed through combinatorial chemistry and high throughput screening of particulate solids. Poor solubility and bioavailability of these pharmaceuticals are challenging attributes confronted by a formulator during product development. Hence, substantial efforts have been directed into the research on particle generation techniques. Although the conventional methods, such as crushing or milling and crystallization or precipitation, are still used; supercritical fluid technology introduced in the mid-1980s presents a new method of particle generation. Supercritical fluid processes not only produce micro- and nanoparticles with a narrow size distribution, they are also employed for the microencapsulation, cocrystallization, and surface coating with polymer. Recognized as a green technology, it has emerged as successful variants chiefly as Rapid Expansion of supercritical solutions (RESS), Supercritical anti-solvent (SAS) and Particles from Gas Saturated Solution (PGSS) depending upon type of solvent, solute, antisolvent and nebulization techniques. Being economical and eco-friendly, supercritical fluid technolgy has garnered considerable interest both in academia and industry for modification of physicochemical properties such as particle size, shape, density and ultimately solubility. The current manuscript is a comprehensive update on different supercritical fluid processes used for particle generation with the purpose of solubility enhancement of drugs and hence bioavailability.